2019–2020 Florida Citrus Production Guide: Citrus Under Protective Screen (CUPS) Production Systems - Arnold W. Schumann; Ariel Singerman; Alan L. Wright; Rhuanito S. Ferrarezi (EDIS)
This 2-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by A. W. Schumann, A. Singerman, A. L. Wright, and R. S. Ferrarezi, and published by the Horticultural Sciences Department, March 2019.